A Study on Wetting Phenomena and Measurement Method of a Contact Angle - FUJITA, Hideomi; SASAKI, Hideharu; KATOH, Kenji (Nihon Kikai Gakkai rombunshuu. B hen, 1988)
The purpose of this study is to investigate the mechanism of wetting from a macroscopic viewpoint. The liquid meniscus formed under a conical solid surface is chosen as the subject of the theoretical analysis. The meniscus configuration is obtained by solving the Laplace equation numerically, and using this result, the total energy of the system is calculated. In the case of the half vertical angle of the cone φ=90° (horizontal plate), the system shows thermodynamic instability when the meniscus attaches to the solid surface at the contact angle. This fact, unlike a popular view, explains the wetting phenomena observed in this report. On the other hand, when 0°<φ<90°, the system shows thermodynamic stability at the contact angle. However, when the solid cone is held at a position higher then the critical height from a static liquid surface, the system becomes unstable. It is possible to measure the contact angle easily using this unstable phenomenon.